A comparative study on law regulating cybersquatting in the United States of America and Malaysia / Muhammad Farid Omar … [et al.] - Omar, Muhammad Farid; Abd Rahman, Muhammad Fuad; Mohd Zainal, Nadia Ezzati; Ismail, Nurul Hanani (2013)
Cybersquatting was already an alarming issue throughout the whole world in these millennia. However through our observations in general, we see and discover that some regional minds especially for our scope, which is the proud and loving country of Malaysia have no significance stress on this issue as the heat of this offence either in the eye of the public as well as the Malaysian law itself, shows no inducement of seriousness in the aftermath of such offence. It may be fair to say that maybe the urge for development in this issue had not reach its peak in climax for an evolution and imposition for a much more perfected operation of law instead of only a functional one, but do we really need to actually wait for this issue to reach an alarming height where only then that we should take this offence seriously?. Due to this, we had decided to compare the United States of America's development of law against cybersquatting and make it our guideline of prevention in contrast with our country. Thus in this research, we had humbly highlighted the history of development of both the offence of cybersquatting as well as the stages in development of the Act that had emerged in governing them in both USA and Malaysia. With the degree of comparison with Malaysia, we had thus concluded that the same implementation that the USA had done in their cybersquatting Act should be done to Malaysian Act to improve its certain shortcomings.